Genetically elevated bilirubin and risk of ischaemic heart disease: three Mendelian randomization studies and a meta‐analysis. (20th August 2012) - Stender, S.; Frikke‐Schmidt, R.; Nordestgaard, B. G.; Grande, P.; Tybjærg‐Hansen, A.
Abstract Background Elevated plasma levels of bilirubin, an endogenous antioxidant, have been associated with reduced risk of ischaemic heart disease (IHD) and myocardial infarction (MI). Whether this is a causal relationship remains unclear. Objective We tested the hypothesis that elevated plasma bilirubin is causally related to decreased risk of IHD and MI. Design We used a Mendelian randomization approach and three independent studies from Copenhagen, Denmark. We measured bilirubin in 43 708 white individuals from the general population, and genotyped rs6742078 G>T in the uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) gene in 67 068 individuals, of whom 11 686 had IHD. Results Third versus first tertile of baseline bilirubin levels was associated with 134% increased bilirubin levels, with sex‐ and age‐adjusted hazard ratios (HRs) of 0.86 [95% confidence interval (CI), 0.76–0.98; P = 0.02] for IHD and 0.81 (95% CI, 0.66–0.99; P = 0.04) for MI, but with corresponding multifactorially adjusted HRs of 0.93 (95% CI, 0.82–1.06; P = 0.29) and 0.90 (95% CI, 0.73–1.12; P = 0.35). UGT1A1 rs6742078 TT versus GG genotype was associated with 95% increased bilirubin levels (P < 0.001); TT versus GG genotype was associated with odds ratios (ORs) of 1.03 (95% CI, 0.96–1.11; P = 0.73) for IHD and 1.01 (95% CI, 0.92–1.12; P = 0.68) for MI. Finally, in a meta‐analysis of the present three studies and eight previous studies including a total of 14 711 cases and 60 324 controls, the random effects OR for ischaemic cardiovascular disease for genotypes with approximately 100% increased bilirubin levels versus reference genotypes was 1.01 (95% CI, 0.88–1.16). Conclusion These data suggest that plasma bilirubin is not causally associated with risk of IHD.